Wither health science librarianship? Many questions, many options. (5th June 2019) - Murphy, Jeannette
Abstract: The 2019 virtual issue of the Health Information and Libraries Journal (HILJ) is published to link to the 2019 EAHIL Workshop taking place in Basel, Switzerland on 17‐20 June 2019. The workshop is structured around six topics: (i) Roadmap of our Profession; (ii) Technology Uptake; (iii) Ecology of Scholarly Communications; (iv) Impact + Assessment; (v) Benchmarking + Advocacy; (vi) Evidence‐Based Practice. These themes have been used to compile this virtual issue, which contains published articles selected from HILJ from the March 2019 issue through to June 2017. The virtual issue mirrors the format of a regular issue of HILJ, namely a review article, five original articles and articles from our three regular features: 'Dissertations into Practice', 'International Perspectives and Initiatives' and 'Teaching and Learning in Action'. The authors come from the UK, Canada, Australia, Italy, Iran and Belgium. All articles included in this virtual issue are available free online.